Heritage Conservation and Social Engagement - Peters, Renata F.; den Boer, Iris L. F.; Johnson, Jessica S.; Pancaldo, Susanna; Peters, Renata F.; den Boer, Iris L. F.; Johnson, Jessica S.; Pancaldo, Susanna (London UCL Press, 2020)
Heritage Conservation and Social Engagement explores different kinds of engagement, participation, access, and creative use of resources motivated by the practice of conservation, and offers ethical and practical perspectives from which to approach cultural heritage projects. The chapters are structured around the themes of engagement and participation, with an emphasis on the value of cross-disciplinary collaborations and the adoption of more encompassing approaches to conservation decision-making. The authors explore the complexities of these collaborations, which are often influenced by the colonial baggage of museums and whose effectiveness vary according to context, objectives, methods and resources available. Given the variable nature of the factors involved, providing evidence for the beneficial impacts of engagement is not always a straightforward task. For a strong body of evidence to be formed, it is essential that conservators continue to create spaces to debate methods that may open new frontiers. Efforts to promote inclusion and engagement through museum collections and the broader heritage sector are becoming even more socially relevant, as in recent years we have observed a rise in intolerance towards minority groups in traditionally democratic societies. The heritage sector is responding strongly, however, as it has the tools to help fight prejudices that are invariably based on misinformation or manipulation of facts. This book joins these efforts, in the knowledge that nothing can be done without dialogue and engagement.
English
Keywords: Museology & heritage studies; archaeology; heritage; conservation; social engagement; preservation; museums; cultural heritage; heritage management; museology